Scholarship in Academic Surgery: History, Challenges, and Ideas for the Future - Stein, Sharon L. (Clinics in Colon and Rectal Surgery, 2013)
The role of academic surgery is changing. Traditional roles of the triple threat researcher, clinician and teacher, were formulated by Osler and improved upon by Boyle in the 1990s. These include application and integration of research to clinical problems. However, new pressures exist on the academic surgeon. Financial pressures rising costs of health care and decreased research funding all need to be addressed. In addition, retention and advancement of faculty is more difficult with increased emphasis of clinical practice in academic medicine. The future of academic medicine will require personal optimization as a multifaceted academician, businessman, and administrator, as well as rethinking how academic medicine may function in the future.
Keywords: academic surgery; domains of scholarship; academics; surgical faculty